Pembelajaran Musik dalam Stimulasi Pengembangan Kemampuan Sosial Emosinal Anak Usia Dini - Alifia Nurul Uma; Ali Formen (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Social and emotional development is one aspect of development that must be a primary focus. This is because from an early age, children are expected to be able to live socially, such as having a responsible attitude, working together, feeling empathy towards others, and communicating. This article presents a systematic literature review that aims to determine the effect of music learning in stimulating the development of social and emotional skills in early childhood. The method used in this study is a Systematic Literature Review (SLR). Literature was obtained from electronic databases, namely Google Scholar, journal articles that match the Population, Issue, Output (PIO), children aged 3-5 years, full-text journal manuscripts; research articles with qualitative and quantitative studies that use music as a main component for the development of social and emotional skills in early childhood. The journals used were published in 2022-2026. Article selection was carried out using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method and analyzed using descriptive analysis techniques. A total of 715 articles were considered relevant to the topic, 7 articles were included based on the inclusion criteria. The results of the study show that music learning is effective in improving children's ability to express and regulate emotions, in addition to that, music learning can also improve social interaction, cooperation and empathy.